1991
DOI: 10.1111/j.1463-6409.1991.tb00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Tanqua tiara (Nematoda, Gnathostomidae), and associated lesions in the stomach of the Nile monitor lizard (Varanus niloticus)

Abstract: Tunqua tiara (von Linstow, 1879) Blanchard, 1904 from the stomach of the Nile monitor lizard (Varunus niloticus) in Nigeria is redescribed in detail using both light and scanning electron microscopy. Its mode of attachment and host pathology are described and discussed. A list of hosts and localities from which T. tiara has been recovered is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
2
11
1
Order By: Relevance
“…We found that the stomach walls of keelbacks exhibited severe inflammation and bacterial infection around the sites of Tanqua attachment, similar to findings in other taxa (Pflugfelder ; Naidu ; Gibbons & Keymer ). Based on the sparse gut contents of the worms, they appear to feed, at least in part, on host tissue in the form of inflammatory cells and exudate (Pflugfelder ; Jones ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that the stomach walls of keelbacks exhibited severe inflammation and bacterial infection around the sites of Tanqua attachment, similar to findings in other taxa (Pflugfelder ; Naidu ; Gibbons & Keymer ). Based on the sparse gut contents of the worms, they appear to feed, at least in part, on host tissue in the form of inflammatory cells and exudate (Pflugfelder ; Jones ).…”
Section: Discussionsupporting
confidence: 89%
“…Similar severe inflammatory reactions to Tanqua sp. have been described in snakes and varanid lizards (Pflugfelder ; Naidu ; Gibbons & Keymer ), although not all gastric nematodes invoke a host inflammatory response. Encysted physalopterid larvae, for example, only appear to become infiltrated with immune cells after the larva within has died (Jones ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adults mature in elasmobranchs (Millemann 1963, Troncy 1969, Machida et al 1982, Beveridge 1987, Hoberg et al 1998, Moravec & Nagasawa 2000, Moravec & Justine 2006, characids (Gomes & Kohn 1970, Moravec 2007a, chelonians (Hedrick 1935, Freitas & Dobbin 1971, Berry 1985, S à nchez et al 2006, Roca & Garcia 2008, Muniz-Pereira et al 2009), varanids (Gibbons & Keymer 1991), snakes (Ghadirian 1968), frogs (Morishita 1926) and salamanders (Hasegawa et al 1998). Adults mature in elasmobranchs (Millemann 1963, Troncy 1969, Machida et al 1982, Beveridge 1987, Hoberg et al 1998, Moravec & Nagasawa 2000, Moravec & Justine 2006, characids (Gomes & Kohn 1970, Moravec 2007a, chelonians (Hedrick 1935, Freitas & Dobbin 1971, Berry 1985, S à nchez et al 2006, Roca & Garcia 2008, Muniz-Pereira et al 2009), varanids (Gibbons & Keymer 1991), snakes (Ghadirian 1968), frogs (Morishita 1926) and salamanders …”
Section: Distribution Host Range Site Of Infection and Life Cyclementioning
confidence: 99%
“…Tanqua tiara (T. tiara) is the gastric nematode of Varanus salvator (V. salvator) [1][2][3][4], this worms first identified by [5] as Ascaris tiara and enhanced being genus Tanqua by [6].…”
Section: Introductionmentioning
confidence: 99%